Pt nanoparticles supported over Ce-Ti-O: the solvothermal and photochemical approaches for the preparation of catalytic materials - Adrián M. T. Silva (2010)
Ce-Ti-O supports with different Ce/Ti molar ratios were synthesized by the solvothermal method using hexadecyltrimethylammonium bromide. Pt nanoparticles were then supported by photochemical deposition. The shape, size, and structure of these materials were analyzed by high-resolution transmission electron microscopy. The single CeO(2) support was also prepared, consisting of agglomerated cubic particles ranging from similar to 3 to 8 nm. When titania was combined with ceria, a nanostructured architecture was produced, evidencing the strong influence of Ti in the support structure. Photodeposition of Pt nanoparticles is more efficient on Ce-Ti-O supports than in pristine CeO(2). Crystalline Pt nanoparticles (mainly of similar to 2 to 4 nm) were detected. The catalytic properties of the materials were tested in the selective hydrogenation of cinnamaldehyde to cinnamyl alcohol. It was observed that Pt supported on Ce-Ti-O is more active and selective than Pt on CeO(2) or TiO(2) separately. The catalyst with 40 mol% Ce leads to total conversion of cinnamaldehyde in a few minutes; however, higher selectivity toward the desired product (cinnamyl alcohol) was obtained with higher amounts of Ce (50 mol%).